A study of medical practitioners' preference for print or electronic library materials - Villagracia, Ella S.; Faderon, Rosalie B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
The study focused on the medical practitioner's preference for print and electronic library materials. It was conducted to: (1) determine the level of awareness of the medical practitioners in the UP College of Medicine on the electronic formats in publishing; (2) know which of the two formats they prefer; and (3) look into their information needs.
Out of 230 questionnaires distributed, 214 were returned (92.04 percent): 144 faculty (67.3 percent), 28 researchers (13.1 percent), 6 administrative staff (2.8 percent) and 36 non-employees of the College of Medicine. The findings of the study were based on the results of the questionnaires filled in by the respondents. Descriptive statistics was used in this study.
Findings of the study reveal that medical practitioners prefer the electronic format for the following reasons: (1) Access is quick and easy; (2) time-saving; (3) up-to-date; (4) can be searched and browsed easily; (5) can be printed immediately; (6) it is interactive; and (7) linking is possible.
Results of the survey reveal that medical practitioners visit the library once a week to conduct research. Majority of them search the information they need by themselves. In terms of the tools used as guide in locating the information they need, majority chose the Online Public Access Catalog (OPAC), followed by the printed catalog. Majority of the respondents indicated that they are aware of the availability of the electronic materials in the library; they have used the electronic equipment in the library; and they are familiar with how the materials in electronic form works.
The recommendations for the improvement of the library services at the college of Medicine Library are the following: (1) users should be informed about the new information technologies available in the library; (2) print-based information resources should also be available in electronic version, and information resources stored in electronic form should have printed versions; (3) electronic materials should be user-friendly and (4) there should be integrated library services provided to users.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines (Manila) College of Medicine Library -- Use studies; University of the Philippines (Manila) College of Medicine Library -- Evaluation